Physiological and Productivity of Quail During The Egg-Laying Period with Supplementation of Senduduk (Melastoma Malabathricum L) Powder in Feed - Fredi Kurniawan; Niken Ulupi; Hera Maheshwari (IPB University, 2025)
Quail is a type of poultry that is easy to raise and is the second largest egg producer after laying hens. The benefits of quail include a relatively high production cycle, minimal land requirements, and low feed consumption. Quail are more susceptible to stress compared to other poultry, particularly stress induced by elevated ambient temperatures. This stress can be overcome by administering antioxidants. Melastoma malabathricum L (commonly known as senduduk) leaf is a natural antioxidant that can alleviate stress. This study aimed to evaluate the effectiveness of different doses of senduduk leaf powder on the physiological and performance of laying quails. This study used a Completely Randomized Design with four treatments and four replications. The doses of senduduk leaf powder administered were P0 (0%), P1 (1.5%), P2 (3%), and P3 (4.5%). A total of 160 female quails, aged 40 weeks, were maintained for four weeks. The variables observed comprised hematological values, stress indicators, and quail performance during the laying period. The study’s results on hematological values, stress indicators, and quail performance during the laying period showed an increase at a dose of 3% (P2). The optimal concentration was identified as the 3% dose of senduduk leaf powder in treatment P2.